2018
DOI: 10.1002/jlb.3a0617-261r
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti-inflammatory drugs on the expression of tryptophan-metabolism genes by human macrophages

Abstract: Several lines of evidence link macrophage activation and inflammation with (monoaminergic) nervous systems in the etiology of depression. IFN treatment is associated with depressive symptoms, whereas anti‐TNFα therapies elicit positive mood. This study describes the actions of 2 monoaminergic antidepressants (escitalopram, nortriptyline) and 3 anti‐inflammatory drugs (indomethacin, prednisolone, and anti‐TNFα antibody) on the response of human monocyte‐derived macrophages (MDMs) from 6 individuals to LPS or IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
(166 reference statements)
0
21
0
Order By: Relevance
“…This degradative pathway lowers the immune response through producing various molecules in the kynurenine pathway, including kynurenine, which can bind to the aryl hydrocarbon receptor (AHR) receptor causing immune suppression [67,68]. Regan et al reported depletion in tryptophan with an accumulation of kynurenine following stimulation by LPS and IFN-α [69,70]. The anti-inflammatory drug indomethacin caused a significant attenuation of the effects of LPS on tryptophan and a reduction in the level of kynurenine was observed following IFN-α stimulation, but no effect on kynurenine was observed after LPS treatment [70].…”
Section: Discussionmentioning
confidence: 99%
“…This degradative pathway lowers the immune response through producing various molecules in the kynurenine pathway, including kynurenine, which can bind to the aryl hydrocarbon receptor (AHR) receptor causing immune suppression [67,68]. Regan et al reported depletion in tryptophan with an accumulation of kynurenine following stimulation by LPS and IFN-α [69,70]. The anti-inflammatory drug indomethacin caused a significant attenuation of the effects of LPS on tryptophan and a reduction in the level of kynurenine was observed following IFN-α stimulation, but no effect on kynurenine was observed after LPS treatment [70].…”
Section: Discussionmentioning
confidence: 99%
“…3). We put together four purified human macrophage datasets: (GSE35449, n=21) 25 , (GSE85333, n=185) 26 , (GSE46903, n=384) 27 , (GSE55536, n=33) 28 , and four diverse mouse macrophage datasets: (GSE82158, n=163) 29 , (GSE38705, n=511) 30 , (GSE62420, n=56) 31 , and (GSE86397, n=12) 32 .…”
Section: Resultsmentioning
confidence: 99%
“…We put together four purified human macrophage datasets: (GSE35449, n=21) 25 , (GSE85333, n=185) 26 , (GSE46903, n=384) 27 , (GSE55536, n=33) 28 .…”
Section: Methodsmentioning
confidence: 99%
“…We put together four purified human macrophage datasets: (GSE35449, n = 21) (Beyer et al, 2012), (GSE85333, n = 185) (Regan et al, 2018), (GSE46903, n = 384) (Xue et al, 2014), (GSE55536, n = 33) (Zhang et al, 2015). GSE35449 (PBMC): CD14 + monocytes were isolated from Peripheral blood mononuclear cells (PBMC) using CD14-specific MACS beads and cultured in 6-well plates in media and provided various stimuli: IFN-γ, TNF-α, ultrapure LPS, IL-4, IL-13, or combinations thereof.…”
Section: Data Collection and Annotationmentioning
confidence: 99%
“…To validate TYROBP and FCER1G as universal biomarkers, we interrogated pure macrophage datasets collected from several human and mouse tissues (Figure 3). We combined four purified human macrophage datasets: (GSE35449, n = 21) (Beyer et al, 2012), (GSE85333, n = 185) (Regan et al, 2018), (GSE46903, n = 384) (Xue et al, 2014), (GSE55536, n = 33) (Zhang et al, 2015), and four diverse mouse macrophage datasets: (GSE82158, n = 163) (Misharin et al, 2017), (GSE38705, n = 511) (Orozco et al, 2012), (GSE62420, n = 56) (Grabert et al, 2016), and (GSE86397, n = 12) (Han et al, 2017).…”
Section: Fcer1g and Tyrobp Are Highly Expressed In Purified Macrophagmentioning
confidence: 99%